Quantum interference effect in electron tunneling through a quantum-dot-ring spin valve - Ma Jing-Min; Zhao Jia; Zhang Kai-Cheng; Peng Ya-Jing; Chi Feng (Nanoscale Research Letters, 2011)
Abstract Spin-dependent transport through a quantum-dot (QD) ring coupled to ferromagnetic leads with noncollinear magnetizations is studied theoretically. Tunneling current, current spin polarization and tunnel magnetoresistance (TMR) as functions of the bias voltage and the direct coupling strength between the two leads are analyzed by the nonequilibrium Green's function technique. It is shown that the magnitudes of these quantities are sensitive to the relative angle between the leads' magnetic moments and the quantum interference effect originated from the inter-lead coupling. We pay particular attention on the Coulomb blockade regime and find the relative current magnitudes of different magnetization angles can be reversed by tuning the inter-lead coupling strength, resulting in sign change of the TMR. For large enough inter-lead coupling strength, the current spin polarizations for parallel and antiparallel magnetic configurations will approach to unit and zero, respectively. PACS numbers: